1995
DOI: 10.1074/jbc.270.28.16803
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Histidine 231 in Thermolysin-like Enzymes.

Abstract: In the zinc metallopeptidases produced by the genus Bacillus, an active site histidine has been proposed to either stabilize the transition state in catalysis by donating a hydrogen bond to the hydrated peptide (Matthews, B. W. (1988) Acc. Chem. Res. 21, 333-340) or to polarize a water molecule, which subsequently attacks the peptidyl bond (Mock, W. L., and Aksamawati, M. (1994) Biochem. J. 302, 57-68). Site-directed mutagenesis techniques have been used to change this residue in the zinc endopeptidase from Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
51
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 42 publications
10
51
0
Order By: Relevance
“…Residue in Human ACE C-domain-In thermolysin, thermolysinlike enzymes, and neprilysin, in which the identity of the catalytic His has been confirmed by site-directed mutagenesis (12,13) and x-ray crystallography (14,15), this residue is found C-terminal to the EXXD zinc-binding motif and is preceded by a conserved Asp with 1 or 4 intervening residues. The distance between the EXXD motif and the transition state His is 49 -60 residues in vertebrate neprilysin-like and bacterial thermolysin-like sequences.…”
Section: Prediction Of His 1089 As a Transition State Stabilizingmentioning
confidence: 99%
See 1 more Smart Citation
“…Residue in Human ACE C-domain-In thermolysin, thermolysinlike enzymes, and neprilysin, in which the identity of the catalytic His has been confirmed by site-directed mutagenesis (12,13) and x-ray crystallography (14,15), this residue is found C-terminal to the EXXD zinc-binding motif and is preceded by a conserved Asp with 1 or 4 intervening residues. The distance between the EXXD motif and the transition state His is 49 -60 residues in vertebrate neprilysin-like and bacterial thermolysin-like sequences.…”
Section: Prediction Of His 1089 As a Transition State Stabilizingmentioning
confidence: 99%
“…For example, retro-inverso modification of the amide bond (from -CONH-to -NHCO-) has little effect on inhibitory potencies of mercaptan inhibitors of thermolysin and neprilysin, but this change produces a marked decrease (Ͼ1,000-fold) in ACE inhibitor potency (12,29). These findings illustrate differences in the substrate binding pocket of these gluzincins distal to the site that interacts with the scissile carbonyl bond.…”
Section: Prediction Of His 1089 As a Transition State Stabilizingmentioning
confidence: 99%
“…The members of the thermolysin family are synthesized as inactive precursors, with a large N-terminal propeptide acting as a specific inhibitor for the mature protease and/or an intramolecular chaperone to control the folding of the protease (10,14,20,24). Since the N-terminal propeptide is cleaved by autoproteolysis (9,13,24), a transformant carrying a cloned metalloprotease gene also produces a correctly processed metalloprotease (2,13). On the other hand, studies of metalloproteases from vibrios (4,6,15) have demonstrated that, although these also belong to the thermolysin family, their precursors have C-terminal propeptides as well as N-terminal ones.…”
mentioning
confidence: 99%
“…The new catalytic mutant was generated by mutating H437, an active site histidine involved in stabilizing the transition state during catalysis (3). We also inverted the tags to eliminate the possibility that either tag interfered with substrate binding or catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…The active site zinc ion of these enzymes is coordinated by a water molecule and three amino acid residues, including the two histidines present within the HEXXH motif and a glutamic acid located 20 residues downstream of this motif (2,8). In addition, the glutamic acid residue located within the HEXXH motif and a histidine residue located 83 residues downstream of this motif interact with a water molecule at the active site and are required for catalysis (2,3).…”
mentioning
confidence: 99%